2007
DOI: 10.1161/01.res.0000262688.14288.b8
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculated Right Ventricular Free Wall in the Chicken Heart Forms by Ventricularization of the Myocardium Initially Forming the Outflow Tract

Abstract: Abstract-Recent molecular lineage analyses in mouse have demonstrated that the right ventricle is recruited from anterior mesoderm in later stages of cardiac development. This is in contrast to current views of development in the chicken heart, which suggest that the initial heart tube contains a subset of right ventricular precursors. We investigated the fate of the outflow tract myocardium using immunofluorescent staining of the myocardium, and lineage tracer, as well as cell death experiments. These analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 46 publications
2
61
1
Order By: Relevance
“…There is support from our studies that lengthening of the subpulmonary myocardium of the OFT is active until day 12.5, which is at least one day longer than posed in the literature (Xu et al, 2004;Viragh and Challice 1973) but in line with studies in chick that have indicated contributions to the OFT up to HH24 (correlating with mouse day12.5) (Rana et al, 2007).…”
Section: Developmental Dynamicssupporting
confidence: 90%
See 1 more Smart Citation
“…There is support from our studies that lengthening of the subpulmonary myocardium of the OFT is active until day 12.5, which is at least one day longer than posed in the literature (Xu et al, 2004;Viragh and Challice 1973) but in line with studies in chick that have indicated contributions to the OFT up to HH24 (correlating with mouse day12.5) (Rana et al, 2007).…”
Section: Developmental Dynamicssupporting
confidence: 90%
“…Although the exact time span of cellular addition from the anterior heart field to the myocardial OFT is unclear, addition until embryonic day (E) 11.5 in mouse was previously described (Xu et al, 2004). Using immunofluorescent stainings and deposits of Indian ink in chick, an increase of the myocardial part of the OFT up to stage HH24 has been demonstrated (Rana et al, 2007), corresponding to E12.5 in mouse.…”
Section: Introductionmentioning
confidence: 98%
“…However, we observed an unexpectedly large part of the left ventricular wall to be derived from the embryonic Tbx2 ϩ AVC, whereas the embryonic ventricle, generally assumed to be the precursor compartment of the definitive left ventricle, 20,21,27 only gave rise to the apex, left ventricular septum, and AV bundle. We confirmed the physical relation between the E9.5 AVC and E10.5 left ventricular wall (base) by DiI labeling.…”
Section: Origin and Fate Of The Tbx2mentioning
confidence: 71%
“…Consistently, the primary outflow tract was found to "disappear" mainly through continuous differentiation to ventricular myocardium, with integration of cells into the right ventricular chamber. 27 We propose that slowly proliferating Tbx2 ϩ primary myocardial AVC, inner curvature, and outflow tract cells are marked by Tbx2-Cre. Subsequently, primary myocardial cells (or their daughters) at the border with the ventricular chambers differentiate to Tbx2-negative fast-proliferating chamber myocardium, integrate into the chambers, and rapidly expand to provide a large contribution to the ventricles ( Figure 6A).…”
Section: A Model For Chamber Formation From Primary Myocardiummentioning
confidence: 91%
“…Also, in chicken, it has been shown that cells of the SHF populate the right ventricle. 14 In frogs, that have just one ventricle, cells of the SHF exclusively end up in the OFT. 15 The LIM homeodomain transcription factor Islet (Isl)1 has become a popular molecular marker demarcating the SHF.…”
Section: Early Heart Development: From a Common Progenitor To Differementioning
confidence: 99%